Feto-maternal outcomes following caesarean section: a prospective comparative study at tertiary care centre in North-Western Rajasthan - Kuntal, Neha; Bhat, Madhu Patni; Nimawat, Amit; Yadav, Munmun; Verma, Mahendra Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Caesarean section (CS) is employed when vaginal delivery is not feasible or hazardous to the mother and/or her baby. The procedure, however, is not without risk. We determined the fetomaternal outcomes of CS conducted at P.B.M Tertiary hospital situated in the North-Western region of Rajasthan. Methods: This is a Hospital based prospective comparative study of all CSs performed for various indications at the Dept. of Gynaecology and Obst., S.P. Medical College and P.B.M Hospital, Bikaner, India, from August 01, 2016, to July 31, 2017. All patients who had CS at any time within the 24 h period were noted and followed up until discharge. The sociodemographic data, types of CS, indications, and feto-maternal outcomes were documented in a proforma. Statistical analysis was carried out using the SPSS version 24. Results: There were 16386 deliveries out of which 4456 (27.1%) were by LSCS. The age range of the group A was 21-25 years while in group B it was 26-30 years. The mean age group A was 22.4, and group B it was 27.9 years. Total 6572 primigravida patients delivered and 32.1% had LSCS. Total 9814 multigravida patients delivered and 12.6% had primary LSCS. In group A, 119(79.3%) LSCS were elective as compared to group B where only 19(12.7%) were elective and this difference was found statistically highly significant (p<0.001). Indication of LSCS is different in both the groups. Fetal distress was most common indication in group A (53.3%) while in group B most common indication was APH (35.9%). Perinatal mortality/morbidity was significantly higher in group B (7.3%) as compared to group A (2.7%). Conclusions: The CS rate in this study was 27.1%. Although primary caesarean section in multipara constitutes only a small percentage of total deliveries and caesarean, they are associated with high maternal and perinatal morbidity. The reason for these complications is many. Beside obstetrical causes, factors like lack of antenatal care, low socioeconomic status, anaemia, malnutrition and illiteracy also play a major role obstructed labor and previous CS among Maternal and perinatal complications were more frequent with emergency CS and in the referred cases.